REKSADANA DALAM PRESPEKTIF SYARI’AH - Dimas Roynaldi (IAIN Ambon, 2021)
Mutual funds are an investment instrument that is currently developing in line with the development of the capital market in Indonesia. The difference between Islamic mutual funds and conventional mutual funds lies in the investment policy, this aims to see if there is a difference between Islamic mutual funds and conventional mutual funds. The concept of sharia is actually not strong in its prohibition, but on the advantages and disadvantages and professionalism and economic activity. Keywords: Mutual funds, Sharia mutual funds